2008
DOI: 10.1682/jrrd.2007.11.0181
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture may help motor recovery in chronic stroke survivors: A pilot study

Abstract: Abstract-Past studies have suggested that acupuncture may reduce spasticity in stroke survivors. We do not know, however, whether acupuncture may enhance the effect of strength training on motor function. This study compared upper-limb motor functional improvement in chronic stroke survivors who received a combination of acupuncture and strength training with that of subjects who received strength training alone. A total of 10 chronic stroke patients with moderate or severe wrist muscle spasticity were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 40 publications
(48 reference statements)
0
14
0
4
Order By: Relevance
“…After acupuncture therapy, patients showed improved recovery of motor function, reduced spasticity, relief of post-stroke depression, urinary incontinence or even reduction of infarction sizes (Hu et al , 1993; Johansson et al , 1993; Naeser et al , 1994; Si et al , 1998; Wong et al , 1999; Moon et al , 2003; Alexander et al , 2004; Schaechter et al , 2007; Bai et al , 2008; Liu et al , 2008b; Li et al , 2009b; Liu et al , 2009a; Chau et al , 2010). …”
Section: Acupuncturementioning
confidence: 99%
“…After acupuncture therapy, patients showed improved recovery of motor function, reduced spasticity, relief of post-stroke depression, urinary incontinence or even reduction of infarction sizes (Hu et al , 1993; Johansson et al , 1993; Naeser et al , 1994; Si et al , 1998; Wong et al , 1999; Moon et al , 2003; Alexander et al , 2004; Schaechter et al , 2007; Bai et al , 2008; Liu et al , 2008b; Li et al , 2009b; Liu et al , 2009a; Chau et al , 2010). …”
Section: Acupuncturementioning
confidence: 99%
“…In other studies, acupuncture plus medications showed better effect on total sleep duration than medications alone [25]. In stroke rehabilitation, the study findings indicated that combining EA with strength training treatment reduced muscle spasticity and may have improved the motor function of chronic stroke survivors with moderate or severe muscle spasticity [4]. …”
Section: Introductionmentioning
confidence: 97%
“…Numerous clinical utilizations of acupuncture and planned studies have been developed since the mid-twentieth century. The greatest positive research outcomes were achieved in the areas of pain management [3], stroke-induced paralysis management [4], antiemesis treatment [5], and drug addiction treatment [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Liu et al42 have shown that muscle spasticity was significantly decreased and the active range of motion of the wrist joint was increased after a 6-week combined EA treatment and strengthening exercise intervention. The acupoints used in that study were Hegu (LI 4), Houxi (SI 3), Waiguan (TE 5), Quchi (LI 11), Shousanli (LI 10), and Jianyu (LI 15).…”
Section: Discussionmentioning
confidence: 99%